Statistical Analysis in Clinical and Experimental Medical Research: Simplified Guidance for Authors and Reviewers - Panos GD; Boeckler FM (Dove Medical Press, 2023)
Georgios D Panos,1,2 Frank M Boeckler3,4 1Department of Ophthalmology, Queen's Medical Centre, Nottingham University Hospitals NHS Trust, Nottingham, UK; 2Division of Ophthalmology and Visual Sciences, School of Medicine, Faculty of Medicine and Health Sciences, University of Nottingham, Nottingham, UK; 3Department of Pharmacy and Biochemistry, Eberhard Karls Universität Tübingen, Laboratory for Molecular Design and Pharmaceutical Biophysics, Institute of Pharmaceutical Sciences, Tübingen, 72076, Germany; 4Institute for Bioinformatics and Medical Informatics (IBMI), Eberhard Karls Universität Tübingen, Tübingen, 72076, GermanyCorrespondence: Georgios D Panos, Department of Ophthalmology, Eye & ENT Centre, Queen's Medical Centre, Derby Road, Lenton, Nottingham, NG7 2UH, UK, Tel +44 115 924 9924, Email gdpanos@gmail.com